2020
DOI: 10.1002/wcms.1496
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional ferroelectrics: Candidate for controllable physical and chemical applications

Abstract: The recent emerged two‐dimensional (2D) ferroelectrics have attracted tremendous research interests due to their promising application in nonvolatile electronics devices. The reversible electric polarization of ferroelectrics from the off‐centered positive and negative surfaces can effectively lift the band states near Fermi level and modulate the charge distribution, which therefore play important roles for the controllable electronic/magnetic properties and chemical reactions. Here, based on the latest revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 106 publications
(139 reference statements)
0
23
0
Order By: Relevance
“…The emergence of 2D ferroelectric materials, in particular, the ones with out-of-plane electric polarization, provides an effective approach to tune the electronic and related properties of vdW heterostructures. A number of theoretical designs have been proposed recently to use 2D ferroelectric materials as a functional substrate to tune the electronic, optical, , and magnetic properties of adlayers or the whole heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of 2D ferroelectric materials, in particular, the ones with out-of-plane electric polarization, provides an effective approach to tune the electronic and related properties of vdW heterostructures. A number of theoretical designs have been proposed recently to use 2D ferroelectric materials as a functional substrate to tune the electronic, optical, , and magnetic properties of adlayers or the whole heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stable states should be reversible and nonvolatile to make the control rational. Among various 2D layered materials, 2D ferroelectric (FE) crystals present an intriguing case. That is because 2D FE crystals harbor two stable polarized states (P↑ and P↓) with completely opposite polarized directions, and the polarization that could couple with valleytronics as the effect of FE polarization is equivalent to that of an external electrical field. Moreover, the electrical switching between these two FE states is nonvolatile since the reversed state will be preserved even after removing the external electrical field.…”
Section: Introductionmentioning
confidence: 99%
“…The task of examining a large number of predicted vdW ferroelectrics 63,64,110 to find large polarization material also seems urgent because their experimental confirmed counterparts are not only scarce but also feature small polarization. Exploring vdW multiferroics is equally promising.…”
Section: Discussionmentioning
confidence: 99%
“…We note that thorough reviews of predicted vdW ferroelectrics can be found in other literatures. [61][62][63][64]…”
Section: Introductionmentioning
confidence: 99%